Developing a national network for clinical research: the NIHR Medicines for Children Research Network. (September 2012) - Saint, Gemma L; Poustie, Vanessa; Smyth, Rosalind L
From its formation in 2005 until the present day, the National Institute for Health Research (NIHR) Medicines for Children Research Network (MCRN), in England, has recruited 25, 000 children into over 300 trials. This has been achieved by the formation of a research network infrastructure embedded into the existing NHS led by a national Co-ordinating Center. Through the creation of subspecialty academic groups an extensive yet balanced portfolio has developed, including high-quality clinical trials and other well-designed studies funded by both public-funding bodies and the pharmaceutical industry. This review will describe the vision, mission and objectives of the MCRN from innovation to current structure and will outline its function, achievements and the path it is taking to achieve the vision to improve children's health and alleviate suffering through the provision of better and safer medicines.